Post-operative gamma knife radiosurgery for WHO grade I intracranial meningiomas: A single-center, retrospective study - Yu, Jinxiu; Zeng, Jiamin; Hu, Guanye; Wang, Jing; Chen, Guohao; Huang, Minyi; Liang, Shunyao; He, Yong; Deng, Yinhui; Gong, Ye; Fu, Junyi (Frontiers in Neurology, 2023)
Objective: The aims of this study were to investigate the long-term outcomes of postoperative Gamma Knife radiosurgery (GKRS) for intracranial WHO grade I meningiomas. Methods: One hundred and thirty patients with pathological diagnosis of WHO grade I meningiomas who underwent postoperative GKRS were reviewed in a single center. Results: Fifty-one patients (39.2%) occurred radiological progression after a median follow-up of 79.7 (range, 24.0-291.3) months. The median time to radiological progression was 73.4 (range, 21.4-285.3) months. The radiological progression-free survival (PFS) was 100%, 90%, 78%, and 47% at 1, 3, 5, and 10 years respectively. Thirty-six patients (27.7%) occurred clinical progression. The clinical PFS was 96%, 91%, 84%, and 67% at 1, 3, 5, and 10 years respectively. Twenty-five patients (19.2%) developed GKRS related adverse effects, including radiation-induced edema (n=22). Tumor volume ≥10 ml was associated with radiological PFS (hazard ratio [HR]=1.833, 95% confidence interval [CI]=1.011-3.322, p=0.046) and radiation-induced edema (HR=2.418, 95% CI=1.014-5.771, p=0.047) in multivariate analysis. Of those with radiological progression, 9 patients were diagnosed of malignant transformation. The median time to malignant transformation was 111.7 (range, 35.0-177.2) months. The PFS after repeat GKRS was 49%, and 20% at 3, and 5years respectively. Secondary WHO grade II meningiomas were significantly associated with shorter PFS (p=0.026). Conclusions: Postoperative GKRS was an effective and safe treatment for intracranial WHO grade I meningiomas. Large tumor volume was related with radiological progression. Malignant transformation was one of the main reasons leading to tumor progression after GKRS for WHO grade I meningiomas.